2011
DOI: 10.3390/ph4121518
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ingavirin (6-[2-(1H-Imidazol-4-yl)ethylamino]-5-oxo-hexanoic Acid) Against Human Respiratory Viruses in in Vivo Experiments

Abstract: Respiratory viral infections constitute the most frequent reason for medical consultations in the World. They can be associated with a wide range of clinical manifestations ranging from self-limited upper respiratory tract infections to more devastating conditions such as pneumonia. In particular, in serious cases influenza A leads to pneumonia, which is particularly fatal in patients with cardiopulmonary diseases, obesity, young children and the elderly. In the present study, we show a protective effect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
1
14
0
3
Order By: Relevance
“…F), a controversial influenza inhibitor that is commercially available in Russia. This agent was reported to impair biogenesis and oligomerization of NP in vitro and suppress influenza A and B infections in animal models . However, since its broad antiviral activity encompasses unrelated respiratory viruses, Ingavirin® most likely targets a cellular rather than a virus‐specific component.…”
Section: Strategies To Interfere With the Influenza Virus Polymerasementioning
confidence: 99%
“…F), a controversial influenza inhibitor that is commercially available in Russia. This agent was reported to impair biogenesis and oligomerization of NP in vitro and suppress influenza A and B infections in animal models . However, since its broad antiviral activity encompasses unrelated respiratory viruses, Ingavirin® most likely targets a cellular rather than a virus‐specific component.…”
Section: Strategies To Interfere With the Influenza Virus Polymerasementioning
confidence: 99%
“…Meanwhile, the imidazole derivative ingavirin (51) is an approved anti-influenza drug in Russia [89]. Although its mechanism of action is not absolutely clear, it was suggested that ingavirin also interacts with the influenza virus NP, thus preventing the NP oligomerization necessary for viral replication [90].…”
Section: Inhibition Of Nuclear Import and Export Replication Transcmentioning
confidence: 99%
“…[6,7] More recent research on antiviral properties of 6-azaСyd has demonstrated its high activity relative to human AdV in vitro and in vivo systems. [8][9][10][11][12][13] In cell cultures, the anti-adenoviral effect of 6-azaСyd was expressed by inhibiting the formation of virus-specific intranuclear DNA-containing inclusion bodies, the synthesis of viral proteins and infectious virus. [12,14] The application of 6-azaСyd on a model of disseminated AdV infection in newborn Syrian hamsters led to significant decrease of virus titer and shortening of the time of virus clearance in organs.…”
Section: Introductionmentioning
confidence: 99%